The Relationship Between Low Birth Weight and the Incidence of Stunting in Toddlers 2 Years Old - Sinaga, Desriati; Sinabariba, Merlina; Arisandi, Ermawaty (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stunting is the failure growth in toddlers is due to malnutrition over a long period of time, exposure to repeated infections and lack of stimulation. The period 0-24 months is a golden period that determines the quality of life and is very sensitive because the consequences for the baby during this period will be permanent and cannot be corrected. The aim of this research is to analyze the history of low birth weight and the incidence of stunting in babies. The research design used in this research is a descriptive analytic with retrospective design. The population in this study were 2 years old baby in the working area of the Katarina Simanjuntak Clinic and the sampling technique in this research is a purposive technique, a sampling technique that is based on certain criteria previously determined by the researcher with totaling 98 people. The instrument used in this research was microtoise and KIA Books. The results of data analysis showed that 12 babies with birth weight at risk experienced stunting (24.5%) and 1 person (2%) did not experience stunting with the p value is 0.001, meaning that there is a significant relationship and there was a 15,568 chance of stunting in babies born with low weight compared to babies born with normal weight. This research can used to provide references to health workers in efforts to prevent stunting by optimizing the provision of nutrition and stimulation, especially for babies with low birth weight.